Synthesis and cytotoxic evaluation of some novel 3-[2-(2-phenyl-thiazol-4-yl)-ethyl] -3H-pyrido [2,3-d]pyrimidin-4-one derivatives - Marzieh Rahmani Khajouei; Ghadamali Khodarahmi; Aram Ghaderi (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Pyridopyrimidine and its derivatives have a variety of chemical and biological significances. Thiazole-containing compounds have also been reported to have a wide range of biological activities. Due to the valuable cytotoxic effects of both thiazole and pyridopyrimidinone derivatives, a series of pyridopyrimidinone-thiazole hybrids were synthesized in the present study. Experimental approach: Briefly, different acyl chlorides were reacted with 2-amino nicotinic acid followed by anhydride acetic to give the corresponding pyridobenzoxazinones. The aminothiazole derivative G was also prepared via a multistep procedure and incorporated into the benzoxazinones to furnish the target pyridopyrimidinone, K1-K5. Furthermore, the cytotoxic activity of the final compounds was determined against MCF-7 and HeLa cell lines using MTT assay. Findings/Results: The results indicated that aromatic substitution on C2 of pyridopyrimidine nucleus was in favor of cytotoxic activity on both cell lines, of which, compound K5 bearing a chlorophenyl group showed the highest cytotoxicity. Conclusion and implications: The results of the present study are valuable in terms of synthesis of hybrid molecules and also cytotoxic evaluations which can be useful for future investigations about the design of novel pyridopyrimidinone-thiazole hybrids possessing better cytotoxic activities.